2022
DOI: 10.3389/fneur.2022.938632
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and quality of life in patients with craniofacial movement disorders: A cross-sectional study

Abstract: BackgroundFacial appearance and expressions influence social interaction. Hemifacial spasm (HFS), blepharospasm (BPS), and blepharospasm-oromandibular dystonia (BOD) are common forms of craniofacial movement disorders. Few studies have focused on the mental burden and quality of life (QoL) in patients with craniofacial movement disorders. Therefore, this study investigated mental health and QoL in these patients.MethodsThis cross-sectional study included 90 patients with craniofacial movement disorders (HFS, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…Symptoms of depression are a strong determinator of HR-QoL in dystonia which is in keeping with results of several previous cross-sectional studies in cervical and craniofacial dystonia [ 3 , 9 , 12 ] and other forms of isolated dystonia [ 8 , 30 , 31 ]. In our previous cross-sectional study involving 603 patients from the same cohort including the patients investigated here, and in a study in cervical dystonia, also symptoms of GAD and SAD were associated with all eight subdomains of HR-QoL [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Symptoms of depression are a strong determinator of HR-QoL in dystonia which is in keeping with results of several previous cross-sectional studies in cervical and craniofacial dystonia [ 3 , 9 , 12 ] and other forms of isolated dystonia [ 8 , 30 , 31 ]. In our previous cross-sectional study involving 603 patients from the same cohort including the patients investigated here, and in a study in cervical dystonia, also symptoms of GAD and SAD were associated with all eight subdomains of HR-QoL [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, a recent cross-sectional study in patients with craniofacial dystonia showed similar results using multiple linear regression analysis of depression, anxiety, and SF-36 scores. Anxiety correlated with all eight subdomains of SF36, but after adjusting for disease duration, education level, and depression correlated only with the pain subdomain [ 12 ]. Although depression predicted all subdomains of future HR-QoL in our study, GAD predicted less but relevant subdomains such as general health, emotional well-being and pain and GAD was associated with a significantly lower total QoL as compared to depression (mean HR-QoL: 45.5% ± 17.6 vs. 74.4% ± 16.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After neurostimulation, with the marked improvement of blepharospasm, they could independently ambulate without assistance, as reflected by the improvement (73.9%, p < 0.001) of the 'gait' item in the BFMDRS disability scale [25]. Likewise, the quality of life also significantly improved across various components, including physical functioning, role-physical, general health, vitality and social functioning, which is attributed to the dramatic improvement of dystonic symptoms, as previously reported [26,27].…”
Section: Ta B L Esupporting
confidence: 75%
“…Recent studies have unveiled non-motor features of dystonia, including sleep disorders and depression [27,33], which may play a vital role in the unknown pathophysiology of the disease. In our study, 23.3% of patients with Meige syndrome had sleep disorders, and 55% of those cases preceded the onset of focal dystonia, such as blepharospasm, by an average duration of 9.8 ± 6.6 years.…”
Section: Ta B L Ementioning
confidence: 99%